The Evaluation of the Success about House Nutrition in Improvement Nutrition Status in Semarang (Universitas Negeri Semarang, 2019)
Nutrition is an important factor that directly affects the quality of human resources, health problems and childhood nutrition is a major factor inhibiting the achievement of quality generation. Profile data Semarang City Health Office (2017), cases of malnutrition children year 2013-2016 showed a rising trend. Semarang City Health Office have children malnutrition treatment programs in a comprehensive manner, ie checks and supplementary feeding for malnourished children under five in the